High-throughput phenotyping (HTP) identifies seedling root traits linked to variation in seed yield and nutrient capture in field-grown oilseed rape (Brassica napus L.) - Thomas, Catherine L.; Graham, Neil .S.; Hayden, Rory; Meacham, Mark C.; Neugebauer, Konrad; Nightingale, Mark; Dupuy, Lionel X.; Hammond, John P.; White, Philip J.; Broadley, Martin R. (Oxford Journals, 2016)
Background and Aims. Root traits can be selected for crop improvement. Techniques such as soil excavations can be used to screen root traits in the field, but are limited to genotypes that are well-adapted to field conditions. The aim of this study was to compare a low-cost, high-throughput root phenotyping (HTP) technique in a controlled environment with field performance, using oilseed rape (OSR; Brassica napus) varieties. Methods. Primary root length (PRL), lateral root length and lateral root density (LRD) were measured on 14-d- old seedlings of elite OSR varieties (n 1⁄4 32) using a ‘pouch and wick’ HTP system (~40 replicates). Six field exper- iments were conducted using the same varieties at two UK sites each year for 3 years. Plants were excavated at the 6- to 8-leaf stage for general vigour assessments of roots and shoots in all six experiments, and final seed yield was determined. Leaves were sampled for mineral composition from one of the field experiments. Key Results. Seedling PRL in the HTP system correlated with seed yield in four out of six (r =0.50, 0.50, 0.33, 0.49; P < 0.05) and with emergence in three out of five (r= 0.59, 0.22, 0.49; P < 0.05) field experiments. Seedling LRD correlated positively with leaf concentrations of some minerals, e.g. calcium (r = 0.46; P < 0.01) and zinc (r = 0.58; P < 0.001), but did not correlate with emergence, general early vigour or yield in the field. Conclusions. Associations between PRL and field performance are generally related to early vigour. These root traits might therefore be of limited additional selection value, given that vigour can be measured easily on shoots/ canopies. In contrast, LRD cannot be assessed easily in the field and, if LRD can improve nutrient uptake, then it may be possible to use HTP systems to screen this trait in both elite and more genetically diverse, non-field-adapted OSR.